2005
DOI: 10.1523/jneurosci.2111-05.2005
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Enhancement of the Intrinsic Growth Capacity of Sensory Neurons Combined with the Degradation of Inhibitory Proteoglycans Allows Functional Regeneration of Sensory Axons through the Dorsal Root Entry Zone in the Mammalian Spinal Cord

Abstract: Peripherally conditioned sensory neurons have an increased capacity to regenerate their central processes. However, even conditioned axons struggle in the presence of a hostile CNS environment. We hypothesized that combining an aggressive conditioning strategy with modification of inhibitory reactive astroglial-associated extracellular matrix could enhance regeneration. We screened potential treatments using a model of the dorsal root entry zone (DREZ). In this assay, a gradient of inhibitory chondroitin sulfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
177
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 184 publications
(188 citation statements)
references
References 84 publications
(107 reference statements)
9
177
2
Order By: Relevance
“…Since the regenerated sensory axons did not form synapses with their targets in the brainstem, it remains unknown how synapse formation will affect the physiology of these axons. After dorsal root crush, sensory fibers have been reported to regenerate into the dorsal horn (Ramer et al 2000;Steinmetz et al 2005). Stimulation of the dorsal root also evokes low amplitude, long latency responses within the dorsal horn.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the regenerated sensory axons did not form synapses with their targets in the brainstem, it remains unknown how synapse formation will affect the physiology of these axons. After dorsal root crush, sensory fibers have been reported to regenerate into the dorsal horn (Ramer et al 2000;Steinmetz et al 2005). Stimulation of the dorsal root also evokes low amplitude, long latency responses within the dorsal horn.…”
Section: Discussionmentioning
confidence: 99%
“…Antibody-mediated blockade of growth-inhibitory molecules (Hata et al 2006;Tan et al 2006), enzymatic degradation of growth-inhibitory glycosaminoglycans (GAGs) (Moon et al 2001;Bradbury et al 2002), and pharmacological elevation of cAMP (Qiu et al 2002;Nikulina et al 2004) all promote axon regeneration after spinal cord injury, as does a peripheral nerve conditioning-lesion (Richardson and Issa,1984;Neumann and Woolf, 1999). Combining some of these treatments has resulted in more favorable axon growth patterns (Lu et al 2004;Steinmetz et al 2005;Tan et al 2006), longer fibers (Chau et al 2004;Yin et al 2006), and in some cases, limited behavioral recovery (Pearse et al 2004;Fouad et al 2005).…”
mentioning
confidence: 99%
“…The rapid and long lasting upregulation of proteoglycans within the vicinity of the glial scar has implicated them in the creation of nonpermissive growth environments in the CNS, similar to their role in boundary formation within the CNS during development (Fitch and Silver, 1997b;Grimpe and Silver, 2004;Silver, 1994;Snow et al, 1990). It is now well established that proteoglycans associated with reactive astrocytes clearly inhibit neurite outgrowth in vitro (Bovolenta et al, 1993;Canning et al, 1993;Dou and Levine, 1994;McKeon, et al, 1991;Snow et al, 1990;Tom, et al, 2004b), and these molecules also appear to play a key role in creating an environment that is not appropriate for successful long-distance regeneration of adult neurons after injury in vivo, since their modification allows successful regeneration to occur (Bradbury et al, 2002;Houle et al, 2006;Steinmetz et al, 2005).…”
Section: Molecules Within the Glial Scar Contribute To Regenerative Fmentioning
confidence: 99%
“…In addition to pro-inflammatory cytokines, macrophages can secrete factors that are growth promoting, such as NGF and NT-3 (Elkabes et al, 1996), thrombospondin (Chamak et al, 1994), and IL-1 (Giulian et al, 1994). Even zymosan, a trigger of robust inflammation, when placed in the vitreous chamber of the eye can stimulate regenerating optic nerve fibers (Leon et al, 2000) and when placed into the DRG before root crush appears essential to the success of DRG regeneration into the spinal cord when combined with modification of the extracellular matrix in the CNS compartment (Steinmetz, et al, 2005). Apparently intense inflammatory states created just outside of the CNS illustrate that in certain circumstances inflammation can promote enhanced regeneration by triggering a conditioning-like effect within the neuron (Calvo et al, 2005;Lund et al, 2002;McQuarrie and Jacob, 1991;Wu et al, 2007a).…”
Section: Triggers For the Production Of Inhibitory Extracellular Matrixmentioning
confidence: 99%
“…The enzymes chondroitinase (ChABC) (for review see [148] ) and sialidase [149,150] , or a combination of the two were shown to decrease growth inhibition [151] . Many groups have shown that administration of ChABC is associated with sensory axonal regeneration [152] and functional recovery [148,152,153] when experimentally introduced following SCi. When comparing the two, one group found that sialidase increases axonal regeneration and functional recovery [149][150][151] to a greater degree than either ChABC alone or a sialidase/ChABC combination [151] .…”
mentioning
confidence: 99%